Ischemic Preconditioning Confers Epigenetic Repression of Mtor and Induction of Autophagy Through G9a‐Dependent H3K9 Dimethylation. Issue 12 (December 2016) - Gidlöf, Olof; Johnstone, Andrea L.; Bader, Kerstin; Khomtchouk, Bohdan B.; O'Reilly, Jiaqi J.; Celik, Selvi; Van Booven, Derek J.; Wahlestedt, Claes; Metzler, Bernhard; Erlinge, David
Abstract : Background: Ischemic preconditioning (IPC) protects the heart from prolonged ischemic insult and reperfusion injury through a poorly understood mechanism. Post‐translational modifications of histone residues can confer rapid and drastic switches in gene expression in response to various stimuli, including ischemia. The aim of this study was to investigate the effect of histone methylation in the response to cardiac ischemic preconditioning. Methods and Results: We used cardiac biopsies from mice subjected to IPC to quantify global levels of 3 of the most well‐studied histone methylation marks (H3K9me2, H3K27me3, and H3K4me3) with Western blot and found that H3K9me2 levels were significantly increased in the area at risk compared to remote myocardium. In order to assess which genes were affected by the increase in H3K9me2 levels, we performed ChIP‐Seq and transcriptome profiling using microarray. Two hundred thirty‐seven genes were both transcriptionally repressed and enriched in H3K9me2 in the area at risk of IPC mice. Of these, Mtor (Mechanistic target of rapamycin) was chosen for mechanistic studies. Knockdown of the major H3K9 methyltransferase G9a resulted in a significant decrease in H3K9me2 levels across Mtor, increased Mtor expression, as well as decreased autophagic activity in response to rapamycin and serum starvation. Conclusions: IPC confers an increase of H3K9me2 levels throughout the Mtor gene—a master regulator of cellular metabolism and a key player in the cardioprotective effect of IPC—leading to transcriptional repression via the methyltransferase G9a. The results of this study indicate that G9a has an important role in regulating cardiac autophagy and the cardioprotective effect of IPC.